THE PATIENT’S PERCEPTION OF SERVICE QUALITY AND INTEREST IN RE- VISITS AT SERVICE UNIT OF UNAND HOSPITAL - Yeni Dilla Roza; Ujang Sumarwan; Lilik Noor Yuliati (Jurnal Kesehatan Masyarakat Andalas, 2019)
Every year the number of hospitals has increase in Padang city. This increase intense competition in these hospitals. This is also felt by Andalas University Hospital (RS UNAND) as one of the teaching hospitals in the city of Padang. Therefore UNAND Hospital need to identify the right marketing strategy in dealing with such competition. One marketing strategy that can be carried out by UNAND Hospital is to provide good quality services. This study aims to analyze the relationship between patients’ perceptions about the quality of service and patient’s interest in reusing health services in the outpatient unit of UNAND Hospital. This research uses descriptive method and use questionnaire as tool to get the data. The sampling technique using accidental sampling with cross sectional sampling approach. There are 140  140 respondents as sample, using quantitative descriptive analysis. The conclusion of the study is that there is a significant correlation between patients’ perceptions about the quality of service and patients re-visit. The managerial implications of this is through improving the physician schedules and maintaining and improving service quality.